Developing Trade Relations between Vietnam-Germany - Thi Tinh, Duong (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
More than 40 years of establishing diplomatic relations and developing trade between Vietnam and Germany, it can be seen that Germany is the biggest trading partner of Vietnam in Europe and the largest importer of Vietnam’s exports to the EU. Although the trade between the two countries has not reached expectations, and the results are still inferior to the potential, the prospects for trade between the two countries are great and need to be further developed due to the favorable context and the advantages of the free trade agreement between Vietnam and the EU. This paper analyzes the current state of trade relations between Vietnam and Germany, assesses the advantages and disadvantages, and suggests policy implications for developing trade relations between the two countries in the future. Keywords Vietnam-Germany, trade relations, development prospects, policy implications References [1] European Parliament, “The EU Fruit and Vegetable Sector: Overview and Post 2013”, CAP Perspective, 2011. [2] WTO Center, “EVFTA and the challenges with Vietnam in establishing and operating effective enforcement engagement institutions”, Enterprise News and International Trade Policy, 2014, pp.20-21. [3] Nguyen Anh Thu, Andreas Stoffers, Prospects for Vietnam and Germany in the context of ASEAN and EU economic integration, the 40th anniversary of diplomatic relations between Vietnam and Germany (1975- 2015), Tri Thuc Publishing House, Hanoi, 2015. [4] General Statistics Office (2012, 2014, 2016), Statistical Yearbook, Hanoi. Keywords: Vietnam-Germany, trade relations, development prospects, policy implications. References [1] European Parliament, “The EU Fruit and Vegetable Sector: Overview and Post 2013”, CAP Perspective, 2011. [2] WTO Center, “EVFTA and the challenges with Vietnam in establishing and operating effective enforcement engagement institutions”, Enterprise News and International Trade Policy, 2014, pp.20-21. [3] Nguyen Anh Thu, Andreas Stoffers, Prospects for Vietnam and Germany in the context of ASEAN and EU economic integration, the 40th anniversary of diplomatic relations between Vietnam and Germany (1975- 2015), Tri Thuc Publishing House, Hanoi, 2015. [4] General Statistics Office (2012, 2014, 2016), Statistical Yearbook, Hanoi.